The Relationship between Assessment, Learning Approaches, and Student Satisfaction - Siahaan, Mian; Pardede, Sanggam (Fakultas Ekonomi, Universitas Negeri Semarang, 2023)
The objective of this research is to assess the appropriateness of lecture assessment and its impact on deep learning approaches, surface learning approaches, and student satisfaction. The study was conducted at the Economics Education Study Program, Faculty of Teaching and Education, University of HKBP Nommensen, with a total sample size of 89 individuals. The research methodology employed in this study was quantitative descriptive with survey techniques. Structural Equation Modeling analysis was utilized to examine the compatibility of the structural model depicting the relationships between variables and the available data. The result of this research found the surface learning approach has a significant negative relationship with appropriate assessment of learning, with a regression coefficient of -0.742. The deep learning approach has a significant positive relationship with appropriate assessment of learning, with a regression coefficient of 0.465. The student's satisfaction also has a significant positive relationship with appropriate assessment of learning, with a regression coefficient of 0.335. The surface learning approach and deep learning approach have significant positive influences on student satisfaction, with regression coefficients of 0.026 and 0.236 respectively. Additionally, we recommend conducting further research in the future to expand on these findings.